2015
DOI: 10.3892/ijmm.2015.2348
|View full text |Cite
|
Sign up to set email alerts
|

A novel adamantyl benzylbenzamide derivative, AP736, inhibits melanogenesis in B16F10 mouse melanoma cells via glycogen synthase kinase 3β phosphorylation

Abstract: Recently, much effort has been made to develop effective dermatological depigmenting compounds. In this study, we investigated the novel candidate compound, AP736 (an adamantyl benzylbenzamide derivative), and its effects on melanogenesis in B16F10 melanoma cells, as well as the mechanisms involved. AP736 has been reported to exert anti-melanogenic effects in melanocytes in vitro and in artificial skin equivalents through the inhibition of key melanogenic enzymes and the suppression of the cAMP-protein kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…PI3K activates AKT, which then inhibits GSK3β through phosphorylation at Ser9 (Cross, Alessi, Cohen, Andjelkovich, & Hemmings, ). Recent studies have shown that GSK3β regulates MITF activity (Shin et al, ) but the detailed mechanisms remain unclear. To determine the contribution of PI3K/AKT and GSK3β signaling to melanogenesis, we treated B16F10 cells with the PI3K inhibitor LY294002 and GSK3β inhibitor (2Z,3E)‐6‐bromoindirubin‐3'‐oxime (BIO).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PI3K activates AKT, which then inhibits GSK3β through phosphorylation at Ser9 (Cross, Alessi, Cohen, Andjelkovich, & Hemmings, ). Recent studies have shown that GSK3β regulates MITF activity (Shin et al, ) but the detailed mechanisms remain unclear. To determine the contribution of PI3K/AKT and GSK3β signaling to melanogenesis, we treated B16F10 cells with the PI3K inhibitor LY294002 and GSK3β inhibitor (2Z,3E)‐6‐bromoindirubin‐3'‐oxime (BIO).…”
Section: Resultsmentioning
confidence: 99%
“…MITF gene expression is regulated by many factors, including CREB, PI3K/AKT (Chae et al, ; Hwang et al, ), GSK3β (Shin et al, ), and MAPK (ERK, c‐Jun N‐terminal kinase, and p38; Peng et al, ). In our study, ERK phosphorylation was increased by PA and EP treatment, which corresponded to a decrease in MITF protein level and an increase in ROS generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mushroom TYR activity assay was assessed by measuring DOPA oxidase activity using a slightly modified experimental protocol from a previous study ( 21 ). Briefly, 95 µl of 0.1 M sodium phosphate buffer (pH 6.5) containing the indicated concentrations of kojic acid (50 µM) and MSCE, and 20 µl of mushroom TYR (1,000 U/ml) were combined in each well, and 20 µl of 5 mM l-DOPA was then added.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, when the Wnt pathway is activated by the interactions of Wnt 1, Wnt3a, and Wnt8 with frizzled receptors and low-density lipoprotein receptor-related protein (Lrp) 5/6 co-receptors [ 13 ], GSK3β is negatively regulated. Thereafter, cytoplasmic β-catenin will translocate into the nucleus and bind to the promoter of MITF together with LEF1, resulting in the transcriptional activation of MITF [ 14 , 15 , 16 ]. Another signaling pathway involved in melanogenesis regulation is phosphatidylinositol-3-kinase (PI3K)/Akt signaling.…”
Section: Introductionmentioning
confidence: 99%